Adsorption Isotherms of Caffeine and Theophylline on Metal-Organic Frameworks - Yu Ri Lee; Minglei Tian; Se-Na Kim; Wha-Seung Ahn; Kyung Ho Row (Adsorption Science & Technology)
The adsorption behaviours of caffeine and theophylline on different metal-organic frameworks were examined by comparing their adsorption isotherms. Among C 18 , UIO-66, UIO-66-NH 2 and MIL-125-NH 2 , UIO-66 showed the highest amount of adsorption of target compounds (i.e. caffeine and theophylline). The maximum adsorbed amounts of caffeine and theophylline on UIO-66 were 0.451 and 0.392 mg, respectively. The experimental parameters in the equilibrium isotherms were estimated by linear and non-linear regression analyses. The adsorption equilibrium data of caffeine and theophylline were investigated using the following four models: linear, Langmuir, Freundlich and Langmuir–Freundlich models. Of these models, the Langmuir–Freundlich model showed the best fit. The regression coefficients (r 2 ) of the Langmuir–Freundlich model for adsorption of caffeine and theophylline on UIO-66 were 0.976 and 0.989, respectively.